Ground response of the Kathmandu Sedimentary Basin with reference to 30 August 2013 South-Tibet Earthquake - Rajaure, S.; Koirala, B.; Pandey, R.; Timsina, C.; Jha, M; Bhattarai, M; Dhital, M R; Paudel, L. P.; Bijukchhen, S. (Journal of Nepal Geological Society, 2014)
Ground acceleration of the 30 August 2013 (M4.9), South Tibet Earthquake has been recorded by five accelerometers deployed in the Kathmandu Valley. Analysis of the ground acceleration record reveals that that the EW component was dominant across the valley, and with the exception of one, all stations on sediments recorded PGA much higher than the station on rock. The site response functions, evaluated as the Fourier spectral ratios of the horizontal components on soil relative to the corresponding component on rock, are remarkably similar in the low frequency range (<0.8 Hz) and reveal strong amplification that likely corresponds to basin effects. By contrast, the high frequency site response shows strong variability across the soil sites, likely attributed to the underlying stratigraphy of the shallow soil layers of the valley. The most pronounced differences manifest in the frequency range >2Hz, which is consistent with the variability in PGA across the valley. Because of the small intensity of this event, the empirical site response recorded can be, approximately, considered linear. As such, this study establishes a reference for future studies on nonlinear site response, which is likely to be triggered during future stronger earthquakes.